Perceptions of family physicians regarding patients’ self-medication - BABCINETCHI, Victoria; TIMOTIN, Alina; LOZAN, Oleg (One Health & Risk Management, 2025)
Introduction. Self-medication is the practice of using medications to treat self-diagnosed conditions without prior consultation with a healthcare specialist. This phenomenon is widespread globally, reaching a rate of over 90% in some countries. The objective of the study was to explore and analyze the perceptions of family physicians in the Republic of Moldova regarding self-medication. Material and methods. The study was conducted using descriptive, quantitative, and cross-sectional methods. Data were collected from November 2023 to March 2024 on a sample of 346 family physicians from the Republic of Moldova. Results. It was found that 87.6% of physicians frequently or very frequently encounter patients who resort to self-medication, and 68.79% of physicians have a negative attitude toward this phenomenon. No statistically significant differences were observed between the region, work environment, or work experience of the physicians and the frequency of patients practicing self-medication (p>0.05). A trend was noted of an intensified negative attitude toward self-medication with increasing work experience (p<0.05). At the same time, 55.2% of physicians identified the lack of awareness of the risks associated with self-medication as the main factor driving patients to engage in this practice. Conclusions. Self-medication is frequently observed in the Republic of Moldova, with a primary factor being the lack of awareness, making public education on this issue imperative. The negative attitude toward self-medication increases with the physician’s work experience and is influenced by their own practices. Medical professionals play a decisive role in preventing the risks of self-medication through informing, providing therapeutic advice, and educating patients.